Can the world get along without natural resources? - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2020)
In the distant future, aliens come to Earth. They find a planet devoid of life. Looking closer, the aliens see that life on Earth was once abundant, but was wiped out by a mass extinction. Curiously, this event was driven not by geological disaster, but by one of the extinct species itself. In an orgy of consumption, an odd little animal put the planet under enough stress to drive itself - and the rest of life - extinct. Then comes a startling discovering. Preserved in the sediment lies a document written by a member of the doomed species. What secrets does it contain? The aliens work for years to translate it, hoping that it offers a clue about what drove the species to overconsume. And indeed it does. The document heralds a remarkable delusion: "The world can, in effect, get along without natural resources." What a naive animal, the aliens conclude. While sucking the planet dry, the animal proclaimed its independence from natural resources. No wonder it went extinct.
Keywords: 330; growth; energy; natural resources; neoclassical economics; property